Clinical management of stage III infectious bovine Keratoconjunctivitis associated with Staphylococcus aureus in a dairy cow: a case report - Abdullah, Faez Firdaus Jesse; Adamu, Lawan; Osman, Abdinasir Yusuf; Haron, Abdul Wahid; Saharee, Abdul Aziz (International Organization of Scientific Research, 2013)
A 4 year old female Friesian and Jersey cross breed dairy cattle weighing 300 kg was managed semi-intensively. The case was presented to the Ambulatory unit of the Large Animal Ward, University Veterinary Hospital (UVH), Universiti Putra Malaysia. There was an epiphora of the affected right eye which had increased corneal opacity with episcleral congestion. There was loss of menace reflex of the left eye which indicates loss of sight of the right eye however; there were presence of palpebral reflex on both lateral and medial aspect of the eye. Swab sample of affected right eye was taken using a sterile swab for bacterial culture, isolation and identification. The culture is a mixed growth of Staphylococcus aureus, Pantoa aglomerans, and Staphylococcus intermedius. However, there were no growth of Moraxella bovis or Mycoplasma bovis as these two organisms are the commonly isolated organism in cases of IBK. The therapy was effective and show significant improvement within 30 days of treatment. There were no epiphora observed with reduced corneal opacity and formation of scar tissue in the center of the eye which indicate healing process. Menace and palpebral reflex tests proves positive results for both of the test.